Assessing coral reef resilience for sustainable resource management (case study in Hon La island, Quang Binh province, Vietnam) - Linh, Nguyen Thuy; Tue, Nguyen Tai; Nhuan, Mai Trong (Vietnam Journal of Marine Science and Technology, 2019)
Coral reefs play a crucial role in providing ecosystem services for the coastal communities. However, the resilience of coral reefs is quickly degraded due to both global and local stressors, including climate change and marine pollution. Hon La island in Quang Binh province, Vietnam is one of the most important coral reef ecosystems. However, this area was heavily influenced by human activities and marine pollution. Therefore, the present study is implemented in order to evaluate the resilience of coral reefs in Hon La island for proposing sustainable development solutions. The proposed indicator framework consisted of three dimensions (coral diversity, biodiversity and environment), containing 26 indicators that potentially provided the quantified methods for decision makers to inform a range of management strategies in protecting coral reefs and using natural resources effectively. Results showed that coral reefs in Hon La island had a low resilient index, about 0.369 because of a degradation of diversity, seawater contaminated by oils and the high turbidity. Several solutions were proposed to enhance the resilience of coral reefs, including the establishment of marine protected areas; integrated management of the coastal zone; rehabilitation of coral reefs and application of co-management models. The theoretical framework from the present study could be potentially applied to evaluate the coral reef resilience in other marine areas in Vietnam with appropriate modification.